Kripke o esencializmu izvora materialnih predmetov - Justin, Martin (Analiza: časopis za kritično misel, 2025)
Kripke on Material Origin EssentialismIn the famous footnote 56 of Naming and Necessity, Kripke offers an argument for a claim that material origin is an essential property of objects. It soon became widely accepted in the literature that Kripke was attempting to derive material origin essentialism from his theory of naming alone. It was also argued that he had failed to do so. In this paper, I try to offer a new reading of Kripke’s argument. I argue that the text of footnote 56 should be read as an intuitive argument, based on the same set of intuitions about contingency and necessity that Kripke uses to defend his theory of rigid designators. It turns out that he can only argue for a weak form of material origin essentialism in this way, but I argue that Kripke’s vague formulation of the essentialism thesis is consistent with this weak form as well. First, I present the received view of Kripke’s argument and point out its flaws. I then summarize two approaches to completing the argument and show why they fail. Finally, I present my reading of Kripke’s argument.
Keywords: Saul Kripke; Naming and Necessity; material origin essentialism; rigid designators; intuitive test